Peran Badan Permusyawaratan Desa (BPD) dalam Manajemen Pembangunan Desa Tertinggal di Provinsi Banten - Muhammad Yusuf; Susilowati; Arief Safari (Liquidity, 2026)
This study analyzes the relationship between community participation and the role of the Village Consultative Body (BPD/Badan Permusyaratan Desa) in the governance of disadvantaged village development. Using a qualitative approach with a case study design, the research was conducted on two disadvantaged villages, namely Cinoyong Village (Pandeglang) and Pasindangan Village (Lebak) which were selected purposively based on institutional characteristics and variations in community participation patterns. Data were collected through in-depth interviews, observations, FGDs, and village document reviews, then analyzed using Miles and Huberman's interactive model. The results of the study show that the effectiveness of village governance is highly determined by the quality of interaction between BPD capacity and community participation. Villages with BPD that have high technical capacity, diverse social representation, and a balanced relationship with the Village Head are able to encourage more deliberative and inclusive community participation. On the other hand, the limitations of BPD human resources, the dominance of local elites, and weak documentation of aspirations cause community participation to tend to be instrumental and do not significantly affect policies. This study emphasizes that strengthening the governance of disadvantaged villages requires synergy between increasing the capacity of BPD, providing an inclusive participation mechanism, and improving power relations at the village level. These findings make a conceptual contribution to the study of village governance and offer policy directions to strengthen the sustainable development of disadvantaged villages.